Optimization of Human Resources Performance in the Goods and Services Procurement Work Unit - Riswan, Riswan; Mujahid, Mujahid; Muin, Sri Adrianti (Journal La Bisecoman, 2024)
This study aims to assess the performance of Human Resources and identify factors that affect the performance of Human Resources in the Goods and Services Procurement Work Unit of the Regional Secretariat of Paniai Regency. The research method used is using research with a descriptive qualitative system with data analysis through interview methods and field observations. Key informants we obtained through interviews with 5 people. The results of the study state that the performance of human resources in the Goods / Services Procurement Work Unit of the Regional Secretariat of Paniai Regency has not run optimally, this is due to the unavailability of special functional personnel for the management of Goods / Services Procurement (Working Group), a Procurement System that is still manual, there are internal factors, namely the potential of management officials is not optimal where they have never participated in technical guidance, training or training on the management of goods / services procurement, have never received awards or rewards as a form of appreciation. External factors, namely there is no special budget allocation for improving human resources in UKPBJ and there has been no effort from the government to organize special functional staff for goods / services procurement managers.